Impact of Monetary Policy Rate on Conventional and Islamic Banking - Badar, Munib (International Journal of Economics, 2024)
Purpose: This study examine the role of banking portfolios based on religious philosophy i.e. Islamic banks in comparison of conventional banks of Pakistan to determine whether both of the portfolios of Islamic and conventional banks absorbs monetary policy shocks on the basis of bank specific religious philosophy. Methodology: The study collected quarterly data from 2005 to 2018 from the official sources of the central bank of Pakistan i.e. State Bank of Pakistan and tested by using econometric techniques. The variables include proxy of central bank Policy Rate, Gross Domestic Product and banking portfolios. Findings: The outcome of the study reveals that Islamic philosophy of banks do not contribute significantly in varying effects of monetary policy. Unique Contribution to Theory, Practice and Policy: The government may develop a dual monetary system and introduce pricing mechanisms for Islamic banks separately by introducing sharia-compliant monetary policy instruments to enhance Islamic share in the overall financial plan. Further, a limited number of Sharia advisors who are simultaneously equipped with financial knowledge in another handicap in sharia-compliant product development.